Lecture 4: The 12 key workouts - McMillan, G.
In this lecture, you'll learn the details of each of the key workouts for distance runners along with some information on a few other recommended workouts. You'll find examples for - endurance workouts (recovery runs, long runs, easy runs, marathon goal pace runs), - stamina workouts (steady-state runs, tempo runs, tempo intervals, cruise intervals), - speed workouts (aerobic capacity intervals), - sprint workouts (anaerobic capacity workouts, strides), - other workouts (hill repeats).